Perceptive on bacteriological quality in foods of animal origin sold in the local market: Potential threats for the perishable food supply chain - Aqeel, Afsheen; Ali Mirani, Zulfiqar; Yacoob Bawa, Mariyah; Asif, Saima; Noor, Rabia; Khan, Shumaila; Abbas, Tanveer (International Journal of Endorsing Health Science Research, 2021)
Background: Pre and post-harvest spoilage is becoming a severe concern not only in Pakistan but also worldwide. Foodborne illness remains prevalent throughout Pakistan because of the lack of informed risks and safe handling practices of the food preparers and handlers at each food chain point. It causes food spoilage that results in substantial economic losses to both producers (farmers) and consumers. Therefore, this article aimed to review the microbial load of meat, dairy, and seafood products and how the microbial load/population's shelf life and food quality can be affected. Methodology: During this experimental study, a total 127 samples were collected directly from different industries and included. Total bacterial count (TBC), total coliform count (TCC), fecal coliform count (FCC) and detection of Salmonella were done to check the quality of foods of animal origin collected from the different food industries from 2019 to 2020 and Pakistan standard (P.S.) of food quality was used to compare the results. Results: Among 127 analyzed samples, 27 (34.29%) samples were found contaminated with four bacterial parameters, TBC (6.35%), TCC (19%), and FCC (8.89%). At the same time, Salmonella spp were found absent in all of the samples analyzed. Among seven perishable food commodities, the higher percentage of unsatisfactory samples were observed in the chicken meat (1.62%) and beef meat samples (1.5%), while fresh milk was highly contaminated (0.9%) as compared to the powder milk (0.42%), followed by yogurt (0.26%). Shrimp (0.26%) and fish items (0.2%) showed the least percentage of unsatisfactory samples. Conclusion: The results suggest that a significant quality difference is observed in the food items sold in the central region of Karachi, further representing a vulnerability to human health in terms of bacteriological hazards. Our findings suggest that safety measures should be taken seriously to stay away from possible uncertainties.